Predictors of sepsis, intensive care unit admission, and death in patients hospitalized for complicated skin and soft tissue infections: Retrospective study at a large tertiary-care center - Haifa M. Algethamy; Rufaydah Nasser Alhazmi; Firyal Kamal Alghalayini; Sarah Yasir Bahowarth; Nirmeen M. Bukhari; Layan Bandar Alnosani; Samaher Khalid Dubaei; Razan Abdulelah Sait; Raghad Abdulaziz Mulla; Yasser Abdelghaffar Own; Adel M. Alshabasy (SAGE Open Medicine)
Background: Complicated skin and soft tissue infections often lead to poor health outcomes, with necrotizing skin and soft tissue infections occurring in 70%–80% of hospitalized patients and a mortality rate typically exceeding 20%. The current study’s main objective was to identify early predictors of sepsis, intensive care unit admission, and mortality in hospitalized complicated skin and soft tissue infection patients. Methods: A retrospective review of records from 235 adult complicated skin and soft tissue infection patients admitted from 2012 to 2022 was conducted. Collected data included demographics, medical history, clinical presentation, treatment, and outcomes. Laboratory results were used to calculate the Laboratory Risk Indicator for Necrotizing Fasciitis score for diagnosing necrotizing fasciitis. Predictors of sepsis, intensive care unit admission, and death were identified using logistic regression analysis. Results: Of the 235 patients, 42.1% were wheelchair-bound or bedridden; 93.2% had diabetes, 76.2% had cardiovascular disease, and 33.6% had kidney disease. Necrotizing fasciitis criteria were met by 75% of patients. Sepsis was diagnosed in 27.7% of patients, while 30.6% required intensive care unit admission, and 20.4% did not survive hospital discharge. Low mean arterial pressure and vasopressor use were significant predictors of all three severe outcomes, with pre-existing kidney disease also a predictor of in-hospital death. The Glasgow Coma Scale predicted both intensive care unit admission and sepsis, but not death. Conclusions: Low mean arterial pressure, vasopressor use, and pre-existing kidney disease are key predictors of in-hospital death in patients hospitalized for complicated skin and soft tissue infection. The former two, and the patient’s Glasgow Coma Scale, also appear to predict both intensive care unit admission and sepsis.